Język w społeczeństwie informacyjnym. Wybrane zagadnienia . - Borowiak-Dostatnia, Marta (Investigationes Linguisticae, 2011)
In this paper the author asks questions concerning a language: its role, place and function in the information society. Finding the answers she defines the issues by categorizing the concept of a language in relation to its users and the ICT tools used by these users. As a result they fall into three categories: 1. unintentional users, 2. intentional users and 3. pre-users; each with a set of ICT tools assigned to their group.